Subject Naturalism, Scientism and the Problem of Linguistic Meaning: Critical Remarks on Price's 'Naturalism without Representationalism' - Macarthur, David (Análisis. Revista de investigación filosófica, 2014)
Resumen Huw Price es sin duda uno de los pragmatistas lingüísticos contemporáneos más importantes. Como admirador de su trabajo desde hace mucho tiempo, agradezco la oportunidad de realizar un comentario critico de su inflyente trabajo “Naturalism without Representationalism” (2004) publicado originalmente en un volumen que co-edité con mario De Caro titulado Naturalism in Question. Mis comentarios se centrarán en este trabajo suyo; discutiré cualquier otro material incluido en sus otros trabajos tan solo si sirve para aclarar algún aspect de este trabajo. No discutiré ningún desarrollo reciente de la posición anti-representacionalista de Price.  Palabras clave: Huw Price, naturalismo, representacionalismo, naturalismo del sujeto, cientificismo.   Abstract Huw Price is undoubtedly one of the most important contemporary linguistic pragmatists. As a long-time admirer of his work I welcome this opportunity to critically comment on his influential paper, “Naturalism without Representationalism” (2004), that first appeared in a volume I co-edited with Mario De Caro titled Naturalism in Question. My comments will be focused mainly on this paper; material from other papers will only be discussed in so far as it helps elucidate themes in this paper. I shall not be discussing recent refinements in Price’s anti-representationalist position.  Keywords: Huw Price, naturalism, representationalism, subject naturalism, scientism.